(3aJM ef dg Cf jef HGdcdGes - (3Gdehdhj MSf GdReGfs ((3ecI GdecQeIs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai GeG HYO abO SFdJ aj GdMQejf GdecQejf Gf GJcde aj LRA Ydi eG jDKQ ef JQLeGf GdbQBf YHO Gddg Hf YHGS aj bhdg NUUfG Hbhdg hef GdCQV eKdgf bO SejJ GdLRA aJM ef dg Cf jef HGdcdGes
(3BNQgG (B:s
(3GdOhQI GdChdi efShHG EdjfG HGWfG Cj Edi eMeO Udi Gddg Ydjg hBdg hSde haj GdXGgQ efShHG Edi ef jfSH Edjg ef TQY EHQGgje hehSi hYjSi hLejY GdCfHjGA hGdQSd Edi BNQ HjGfg faY Gddg HYQaGfgs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs